2020
DOI: 10.1136/bmjopen-2020-038182
|View full text |Cite|
|
Sign up to set email alerts
|

Screening tools for early identification of children with developmental delay in low- and middle-income countries: a systematic review

Abstract: ObjectiveTo systematically review, identify and report the screening tools used for early identification of developmental delay in low- and middle-income countries.DesignSystematic review.Data sourcesFour bibliographic databases: Medline (1946 to 13 July 2020), Embase (1974 to 13 July 2020), Scopus (1823 to 11 July 2020) and PsycINFO (1987 to July week 1 2020).Eligibility criteriaPeer-reviewed original articles published in English addressing validated culturally sensitive developmental screening tools among c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 57 publications
0
29
0
3
Order By: Relevance
“…The effective users of the CARE booklet in this study were the 85.2% of receivers who used it for 1 month at home. The high level of CARE report use has considerable positive implications for the whole monitoring, screening and surveillance cycle to track a child’s developmental progress ( Faruk et al, 2020 ), known as the detection-intervention-prevention continuum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective users of the CARE booklet in this study were the 85.2% of receivers who used it for 1 month at home. The high level of CARE report use has considerable positive implications for the whole monitoring, screening and surveillance cycle to track a child’s developmental progress ( Faruk et al, 2020 ), known as the detection-intervention-prevention continuum.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies reported low delay prevalence in DS ( Ozturk-Ertem et al, 2019 ) and the higher prevalence in our study must be interpreted with caution. If excluding participants to receive the CARE booklet after first screening is a recruitment bias, it is an opportunity for methodological improvement since several barriers to the identification of developmental delay using tools adapted for LMIC have recently been reported ( Faruk et al, 2020 ). Indeed, other screening studies include samples that did not share comparable sociodemographic characteristics to our participants, such as lower socioeconomic status ( Murphy et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate screening, surveillance and assessment for early identification with relevant tools for DD in low to middle income countries (LMICs). 1 , 10 …”
Section: Promoting Early Intervention At Primary Healthcare Levelmentioning
confidence: 99%
“…To review the tools used and promote use of appropriate instruments or tests within a PHC context. Govender et al 1 and Faruk et al 10 in a systematic review highlight possible screening tools or tests for LMIC contexts.…”
Section: Promoting Early Intervention At Primary Healthcare Levelmentioning
confidence: 99%
See 1 more Smart Citation